2021
DOI: 10.1039/d1ta07787b
|View full text |Cite
|
Sign up to set email alerts
|

Constructing anion vacancy-rich MoSSe/G van der Waals heterostructures for high-performance Mg–Li hybrid-ion batteries

Abstract: Compared with the strategy of expanding MoS2 interlayer spacing, constructing van der Waals heterostructures of MoS2 and graphene (MoS2/G) has proven to be a more effective method to facilitate the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…It is obvious that the S 2p peaks of SnSSe/C also displayed the same trend as Sn 3d spectra, which also slightly shift to lower binding energy, firmly demonstrating the in situ formation of anion defects in the SnSSe/C. [34,38,39] Additionally, the carbon content of SnSSe/C composite is calculated to be 9.13%, based on the thermogravimetry analysis (TGA) from 30 to 1000 °C in the air atmosphere. (Figure S8, Supporting Information)…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…It is obvious that the S 2p peaks of SnSSe/C also displayed the same trend as Sn 3d spectra, which also slightly shift to lower binding energy, firmly demonstrating the in situ formation of anion defects in the SnSSe/C. [34,38,39] Additionally, the carbon content of SnSSe/C composite is calculated to be 9.13%, based on the thermogravimetry analysis (TGA) from 30 to 1000 °C in the air atmosphere. (Figure S8, Supporting Information)…”
Section: Resultsmentioning
confidence: 70%
“…Compared to the SnS 2 @C sample, the signal for SnSSe/C is distinctively stronger (Figure 1g), indicating that incorporating Se 2− into the SnS 2 crystal could bring extra S vacancies. [34,35] The X-ray diffraction (XRD) pattern of SnSSe/C is presented in Figure 1h; all crystal planes can be well-matched to the standard SnSSe phase, similar to the hexagonal crystalline of SnS 2 @C (JCPDS: 23-0677). Additionally, the S/Se atomic ratio of ≈1.0 is determined by the EDS spectra (Figure S2, Supporting Information), implying the successful formation of SnSSe.…”
Section: Resultsmentioning
confidence: 92%
“…When the current density returns to 50 mA g –1 , the discharge capacity is 272.3 mAh g –1 , which is only marginally lower than the values before the current density increases. Therefore, compared with VS 4 @NC-2, VS 4 @NC-8, or other previously reported cathodes for MLIBs, such as VS 2 , CuS, Nb 2 O 5 , LiTi 2 (PO 4 ) 3 , MoSSe/G, V 2 C, etc., the obtained VS 4 @NC-5 cathode exhibits the best rate capability (Figure f). For comparison, the rate capability of the VS 4 -5 cathode was investigated and is shown in Figure S3d.…”
Section: Results and Discussionmentioning
confidence: 97%
“…54,194,195 In addition to the increased specic capacity and the enlarged interlayer spacing, the incorporation of S or Se can also induce the structural rearrangement and the electron redistribution of MSe 2(1−x) S 2x , leading to the formation of abundant anion vacancies and the metallic phase, which can increase the active adsorption sites and enhance the conductivity of MSe 2(1−x) S 2x . 56,[196][197][198] He et al…”
Section: Alloy Engineeringmentioning
confidence: 99%
“…54,194,195 In addition to the increased specific capacity and the enlarged interlayer spacing, the incorporation of S or Se can also induce the structural rearrangement and the electron redistribution of MSe 2(1− x ) S 2 x , leading to the formation of abundant anion vacancies and the metallic phase, which can increase the active adsorption sites and enhance the conductivity of MSe 2(1− x ) S 2 x . 56,196–198 He et al fabricated MoS 2(1− x ) Se 2 x alloys through partial substitution of S for Se in MoSe 2 . They found that the alloying process can generate anion vacancies, and the vacancy concentration can be adjusted by tuning the ratios of S and Se.…”
Section: Molecular Modulation Strategies For Tmds In Metal Ion Batteriesmentioning
confidence: 99%